Electroacupuncture pre-treatment alleviates sepsis-induced cardiac inflammation and dysfunction by inhibiting the calpain-2/STAT3 pathway - Li, Xuqing; Wang, Li; Ying, Xinwang; Zheng, Yujun; Tan, Qianqian; Yu, Xiaolan; Gong, Jiahong; Li, Ming; Deng, Xiaofeng; Yang, Guanhu; Li, Shengcun; Jiang, Songhe (Frontiers in Physiology, 2022)
Electroacupuncture (EA) has both anti-inflammatory and cardio-protective effects. Activation of calpain pathway is involved in several myocardiopathy. In sepsis, the role of calpain-2-regulated STAT3 in cardio-protective mechanism of electroacupuncture remains unclear. In this study, we aimed to elucidate the mechanism by which electroacupuncture reduces cardiac inflammation and apoptosis and improves cardiac function during sepsis. Electroacupuncture pretreatment for 7 days was applied in septic cardiomyopathy model induced by lipopolysaccharide (LPS). lipopolysaccharide-induced sepsis was associated with a dramatically systemic inflammation and cardiac dysfunction, which was alleviated by electroacupuncture pre-treatment. Lipopolysaccharide resulted in increases of pro-inflammatory factors (TNF-α,IL1βand IL-6) and apoptosis (TUNEL staining and BAX/Bcl2) via activation of calpain-2/STAT3 pathway.Electroacupuncture pre-treatment inhibited LPS-induced activation of cardiac calpain-2/STAT3 signalling and ameliorated inflammatory and apoptosis. Additionally, inhibition of calpain-2 expression using the corresponding siRNA decreased the Phosphorylation of STAT3,pro-inflammatory factors and apoptosis in lipopolysaccharide- treated cardiomyocytes, confirming that calpain-2 activated p-STAT3 participate in septic cardiomyopathy. Furthermore, suppression of STAT3 by stattic enhanced anti-inflammatory and anti-apoptosis effects of electroacupuncture. These findings reveal mechanisms of electroacupuncture preconditioning protection against cardiac inflammation and apoptosis in sepsis mouse via calpain-2/STAT3 pathway and may provide novel targets for clinical treatments of the sepsis-induced cardiac dysfunction.